Clinical study of ocular manifestations in patients with newly diagnosed and relapsed hematolymphoid malignancies at a tertiary care hospital - Deepthi Rameshbabu Honniganur; Thanuja Gopal Pradeep; Santhosh Kumar Devadas (Journal of Clinical Ophthalmology and Research, 2024)
Objectives: To estimate the proportion of ocular manifestations in new and relapsed cases of various hematolymphoid malignancies and to determine an association between these ocular manifestations and the hematological parameters of the patients. Materials and Methods: The study was conducted in the department of ophthalmology in association with medical oncology. All patients with newly diagnosed or presenting with a relapse of hematolymphoid malignancies underwent a complete ocular evaluation. Results: A total of 63 patients were included in this study. The mean age of the patients was 34.71 ± 19.80 years. Acute myeloid leukemia and B-ALL accounted for 73% of the cases. At the time of examination, 47.61% of patients (n = 30) were newly diagnosed and 52.38% (n = 33) had relapsed. Acute leukemias had more probability of having ocular manifestations than chronic leukemias (P = 0.01). Subconjunctival hemorrhage was found to be the most common anterior segment finding (n = 10, 15.87%; P = 0.05). The most common posterior segment finding seen in both the right and left eyes was dot blot hemorrhages (n = 20). Those patients who had hemoglobin counts <6.5 mg/dl had the most ophthalmic manifestations (n = 20); of which Roth spots were seen the most (n = 6; P = 0.04). And those who had platelet counts <50,000 cells/cumm presented with Roth spots (n = 6, P = 0.05) followed by subretinal hemorrhages (n = 5, P = 0.05) and preretinal hemorrhages (n = 5, P = 0.05). Conclusion: Screening to detect ocular manifestations is of importance in hematolymphoid malignancy, especially in newly detected and relapsed cases. A complete ocular examination is recommended in these patients, as most patients are asymptomatic and ocular manifestation could be an early sign of worsening of the disease. Among the various blood parameters, low hemoglobin and platelet counts are definite indicators of the presence of intraretinal bleeding manifestations.